2022
DOI: 10.1108/irjms-07-2021-0055
|View full text |Cite
|
Sign up to set email alerts
|

Comovement of stock markets after the first COVID wave: a study into five most affected countries

Abstract: PurposeThe purpose of this paper is to look at the contemporaneous movement of the stock market indices of the five most COVID-infected countries, namely, the USA, Brazil, Russia, India and UK after the first wave along with market indices of the three least affected countries, namely, Hong Kong, South Korea and New Zealand during the first wave.Design/methodology/approachData have been collected from the website of Yahoo finance on daily closing values of five indices. Augmented Dickey–Fuller test with its th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Furthermore, there is almost consensus among studies results during covid-19 that an increase rapidly in the number of covid-19 deaths led to a decline in financial assets value except for gold (Kyriazis, 2021). A number of studies found during the Covid-19 the relatedness and interdependence among the regional or global stock market indicators (Youssef et al, 2021;Al-Najjar, 2022), while a few studies' results indicated weak connectedness and inverse relationship between the local and the international equity markets even under the impact of the Covid-19 pandemic (Amewu et al, 2022;Das and Gupta, 2022). Not very many studies during the Covid-19 found a negative relationship between the currency exchange rate and the stock market (Syahri and Robiyanto, 2020;Nwosa, 2021), while no study mentioned any positive relationship between the exchange rate and stock market during the pandemic, but some indicated that there was no evidence of any interaction at all (Chaudhry et al, 2021;Kumar and Robiyanto, 2021).…”
Section: During the Pandemic Of Covid-19mentioning
confidence: 99%
“…Furthermore, there is almost consensus among studies results during covid-19 that an increase rapidly in the number of covid-19 deaths led to a decline in financial assets value except for gold (Kyriazis, 2021). A number of studies found during the Covid-19 the relatedness and interdependence among the regional or global stock market indicators (Youssef et al, 2021;Al-Najjar, 2022), while a few studies' results indicated weak connectedness and inverse relationship between the local and the international equity markets even under the impact of the Covid-19 pandemic (Amewu et al, 2022;Das and Gupta, 2022). Not very many studies during the Covid-19 found a negative relationship between the currency exchange rate and the stock market (Syahri and Robiyanto, 2020;Nwosa, 2021), while no study mentioned any positive relationship between the exchange rate and stock market during the pandemic, but some indicated that there was no evidence of any interaction at all (Chaudhry et al, 2021;Kumar and Robiyanto, 2021).…”
Section: During the Pandemic Of Covid-19mentioning
confidence: 99%
“…This technique was originated by Granger (1986) and Johansen (1988) and has been widely applied in investigating stock market integration like Taylor et al (1989), Kasa (1992), Gulzar, Mujtaba Kayani, Xiaofen, Ayub, and Rafique (2019) etc. Das and Gupta (2022) used Johansen cointegration test to examine the comovement of stock indices of five most COVID affected nations after first wave along with the market indices of three least affected nations during the first wave. The study found evidence of cointegration between different indices during the pandemic period and no integration between least three COVID-affected countries during the pandemic time.…”
Section: Comovement Of Stock Marketsmentioning
confidence: 99%